Selectins and their counter receptors: a bitter sweet attraction. Issue 11 (November 1996) - Symon, F A; Wardlaw, A J
Abstract : Selectins are adhesion receptors expressed by leucocytes, platelets, and endothelial cells. They mediate the initial binding of leucocytes to vascular endothelium in the post-capillary venules. This is an essential first step in leucocyte migration into tissue. The selectin family of adhesion receptors consists of three C-type lectins (E, P, and L selectin). Their ligands (counter structures) are sialylated and fucosylated carbohydrate molecules which, in most cases, decorate mucin-like glycoprotein membrane receptors. Studies using blocking monoclonal antibodies have shown that inhibition of selectin function can ameliorate a range of inflammatory processes, offering the possibility that antagonists of selectin function may be useful in the treatment of inflammatory lung diseases such as asthma.